Navigating The Modern Teaching Methods for Applied Psychology (Eurasian Scientific Herald, 2023)
This comprehensive article explores the essential requirements for teaching applied psychology in the modern educational landscape. Covering aspects from a versatile curriculum and technological integration to ethical considerations and cultural competence, the article underscores the need for educators to adapt their approaches. It addresses the diverse needs of students, emphasizing experiential learning, continuous assessment, and global perspectives. The inclusion of mentorship programs, flexibility in assessment methods, and emerging specializations further highlights the evolving nature of applied psychology education